ECONOMIC EDUCATION ON THE PUGER BEACH FISHERMAN FAMILY - Ani, Hety Mustika; Widjaja, Sri Umi Mintarti; Soetjipto, Budi Eko; Wahyono, Hari (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
The urgency of family economic education, especially among the fishing communities of Puger coastal area, Jember Regency, needs to be addressed to achieve welfare. The internalisation process that occurs needs to be examined in depth to ensure no party is disadvantaged. This study aims to describe the role of parents in internalising economic education to their children within fishing families and to identify the forms of economic education processes that take place within them. This research is a qualitative phenomenological study with purposive sampling to obtain in-depth knowledge about the economic education of fishing families. Data validation uses technique and source triangulation, analysed with the Miles & Huberman framework, assisted by NVivo 12 Plus software. The findings reveal the uniqueness and advantages of the family economics education for fishermen, which has developed rapidly, not only verbally but also through examples, habituation, and open discussions. The implications of this research theoretically suggest that economic education is more than traditional, but interactive. In practice, the role of parents alongside children is important for the economic welfare. The best policy is to maximise the welfare of fishermen and the future of fishermen's children who must struggle with limited economic resources.